1. ## hyperbolas

> "36x^2 - 100y^2 - 72x + 400y = 3928"
In the standard Hyperbola form >
All I know is that I need to start by "Factoring" the original equation, but I'm not to sure even how to do that

Thanks

2. Hi

Here is the beginning

$36x^2 - 100y^2 - 72x + 400y = 3928$

$36(x^2 - 2x) - 100(y^2 - 4y) = 3928$

$36((x-1)^2 - 1) - 100((y-2)^2 - 4) = 3928$

$36(x-1)^2 - 100(y-2)^2 = 3928 + 36 - 400$

3. ## hyperbola standard form

I had to put this equation > 36x^2 - 100y^2 - 72x + 400y = 3928
in this form
With Help I got to this stage
36(x-1)^2 - 100(y-2)^2 = 3928 + 36 - 400
and then
36(x-1)^2/99 - 100(y-2)^2/35.64 but the simple form has a^2 and b^2 and I cant find the square root of 99 and 35.64 which leads me to beleive that im wrong, please help.

4. Originally Posted by 14041471
I had to put this equation > 36x^2 - 100y^2 - 72x + 400y = 3928
in this form
With Help I got to this stage
36(x-1)^2 - 100(y-2)^2 = 3928 + 36 - 400
and then
36(x-1)^2/99 - 100(y-2)^2/35.64 but the simple form has a^2 and b^2 and I cant find the square root of 99 and 35.64 which leads me to beleive that im wrong, please help.
Why can't you take the square root of those numbers? They're both positive. They're just not perfect squares.

5. Originally Posted by 14041471
I had to put this equation > 36x^2 - 100y^2 - 72x + 400y = 3928
in this form
With Help I got to this stage
36(x-1)^2 - 100(y-2)^2 = 3928 + 36 - 400
and then
36(x-1)^2/99 - 100(y-2)^2/35.64 but the simple form has a^2 and b^2 and I cant find the square root of 99 and 35.64 which leads me to beleive that im wrong, please help.
I believe this is what you should have:

$\frac{(x-1)^2}{99}-\frac{(y-2)^2}{35.64}=1$